Предмет: Алгебра,
автор: Jnozan
помогите плииз срочно
Приложения:
Ответы
Автор ответа:
0
(3^6*15^-5)/(5^-4)=
=(3^6* (3*5)^-5/(5^-4)=
=(3^6 * 3^-5 * 5^-5)/ (5^-4)=
=3 * 5^-5 * 5^4=
=3 * 5^-1=
=3/5=
=0.6
=(3^6* (3*5)^-5/(5^-4)=
=(3^6 * 3^-5 * 5^-5)/ (5^-4)=
=3 * 5^-5 * 5^4=
=3 * 5^-1=
=3/5=
=0.6
Автор ответа:
0
Всё понятно?
Автор ответа:
0
да спасибо
Автор ответа:
0
извините * это что означает
Автор ответа:
0
это умножить
Похожие вопросы
Предмет: Музыка,
автор: profiggprocpp
Предмет: Русский язык,
автор: Аноним
Предмет: Алгебра,
автор: lracom1986
Предмет: Математика,
автор: Mike53